Electrophysiological Correlates of the Threshold to Detection of Passive Motion: An Investigation in Professional Volleyball Athletes with and without Atrophy of the Infraspinatus Muscle. (14th January 2013) - Salles, José Inácio; Cossich, Victor Rodrigues Amaral; Amaral, Marcus Vinicius; Monteiro, Martim T.; Cagy, Maurício; Motta, Geraldo; Velasques, Bruna; Piedade, Roberto; Ribeiro, Pedro
Abstract : The goal of the present study is to compare the electrophysiological correlates of the threshold to detection of passive motion (TTDPM) among three groups: healthy individuals (control group), professional volleyball athletes with atrophy of the infraspinatus muscle on the dominant side, and athletes with no shoulder pathologies. More specifically, the study aims at assessing the effects of infraspinatus muscle atrophy on the cortical representation of the TTDPM. A proprioception testing device (PTD) was used to measure the TTDPM. The device passively moved the shoulder and participants were instructed to respond as soon as movement was detected (TTDPM) by pressing a button switch. Response latency was established as the delay between the stimulus (movement) and the response (button press). Electroencephalographic (EEG) and electromyographic (EMG) activities were recorded simultaneously. An analysis of variance (ANOVA) and subsequent post hoc tests indicated a significant difference in latency between the group of athletes without the atrophy when compared both to the group of athletes with the atrophy and to the control group. Furthermore, distinct patterns of cortical activity were observed in the three experimental groups. The results suggest that systematically trained motor abilities, as well as the atrophy of the infraspinatus muscle, change the cortical representation of the different stages of proprioceptive information processing and, ultimately, the cortical representation of the TTDPM.